Analisis Potensi dan Tantangan Pemanfaatan Bio Solar B30 pada Sistem Pertahanan Nasional - Utomo, Wisnu; Aries Sudiarso; Sri Yanto (Jurnal Serambi Engineering, 2025)
Bio diesel B30 has been implemented as a strategic effort by the government to reduce dependence on fossil fuels and support the development of sustainable renewable energy. This research comprehensively discusses the technical characteristics of B30 bio diesel, the impact of corrosion on non-metallic components in the fuel system, engine combustion efficiency, and the logistical consequences of using bio diesel in the national defense system. The literature study method was used by processing and analyzing various references from accredited scientific journals and current national policies. The results of the analysis show that B30 bio diesel has great potential in supporting national energy security and reducing greenhouse gas emissions, but its implementation requires modernization of storage and distribution systems, comprehensive technical training for personnel, and adaptation of compatible engine technology. Proposed recommendations include phased implementation of pilot projects, development of supporting infrastructure, and integration of bio diesel policy in the defense green strategy to achieve optimal and effective sustainable energy targets.